Analysis of the Effect of Conductor Temperature on Energy Loss in the La-03 Feeder at PT. PLN (Persero) Langsa Power Distribution Unit - Putri Mulia; Hamdani Hamdani; Pristisal Wibowo (Sean Institute, 2026)
Electrical energy losses in distribution systems are one indicator of the efficiency of electricity transmission. One factor influencing the magnitude of technical energy losses is changes in conductor temperature, which cause an increase in conductor resistance. This study aims to analyze the effect of conductor temperature on energy loss in the LA-03 feeder of PT. PLN (Persero) ULP Langsa. The research method used is quantitative analysis with a mathematical calculation approach based on the relationship between conductor temperature, electrical resistance, power losses, and energy loss. The data used includes a feeder length of 6.72 km, A3CS/AAAC conductor type, resistance at a reference temperature of 20°C of 0.3 Ω/km, an average load current of 150 A, a temperature coefficient of 0.004/°C, and an operating time of 24 hours. Calculations were performed at temperatures of 20°C, 40°C, and 60°C. The analysis results show that an increase in conductor temperature from 20°C to 60°C causes resistance to rise from 2.016 Ω to 2.338 Ω. Power losses increased from 45,360 Watts to 52,605 Watts, while daily energy losses increased from 1,088.64 kWh to 1,262.52 kWh. A temperature increase of 40°C resulted in an increase in energy losses of approximately 15.97%. The research results indicate that conductor temperature has a significant effect on the magnitude of energy loss in distribution lines. Therefore, loss calculations in distribution networks should consider actual operating temperatures to obtain more accurate and realistic estimates of energy loss